Réponses

Meilleure réponse !
2014-09-12T09:25:28+02:00
Complète chaque suite logique de  nombres :

a = + 3 - 6 + 12 - 24 + 48 - 96 (de  3 x - 2 = - 6 et - 6 x - 2 = 12, donc 12 x - 2 =  - 24 et - 24 x - 2 = 48, puis 48 x- 2 = - 96

b = + 20 + 13 + 6 - 1 - 8 - 15 (20 - 7 = 13 - 7 = 6 - 7 = - 1 - 7 = - 8 = 7 = - 15)

c = + 1024 - 512 + 256 - 128 + 64 - 32 (1024 : - 2 = 512 : - 2 = 256 : - 2 = - 128 : - 2 = 64 -: - 2 = - 32

d = 500 - 50 + 0,5 - 0,05 + 0,005 (500 : - 10 = - 50 : - 10 = 0,5 : - 10 = - 0,05 : - 10 = 0 , 005

e) -100 + 30 - 9 + 0,9 + 2,7 - 0,81 (- 100 : -10 x 3 = 10 x 3 = 30 ; 30 : - 10 x 3 = - 3 x 9 = - 9 ; 9 : - 10 x 3 = - 0,9 x 3 = 2,7  ; 2,7 : - 10 x 3 = - 0,27 x 3 = - 0,81